Mercado de bovinos de corte: assimetria e transmissão de preços entre os principais mercados exportadores de carne bovina - Caetano, Tulio Ferreira (2019)
The aim of this study is to analyze the price transmission as well as the asymmetry in the price transmission of beef cattle paid to the producer, among the main beef export markets, more precisely: Brazil, the USA and Australia. By the estimation of an autoregressive vector model with error correction (VEC) it could be concluded that the beef cattle markets of the three main beef exporters in the world are integrated concerning the prices paid to producers. The results of the Granger (1987) Causality test in blocks, showed that, in the long term, a change in the price paid to the beef cattle producer in any one of the three analyzed markets causes a change in the prices received by the producers of the other two markets, but the test of asymmetry in price transmission (ATP) pointed to the existence of asymmetry in the transmissibility of increases or decreases in prices between these three markets.